Failure to Replicate the “Work Ethic” Effect in Pigeons - Vasconcelos, Marco (Society for the Experimental Analysis of Behavior, Inc., 2007)
We report six unsuccessful attempts to replicate the “work ethic” phenomenon reported by Clement, Feltus, Kaiser, and Zentall (2000). In Experiments 1–5, pigeons learned two simultaneous discriminations in which the S+ and S− stimuli were obtained by pecking an initial stimulus once or multiple (20 or 40) times. Subsequent preference tests between the S+ stimuli and between the S− stimuli mostly revealed indifference, on average, between the S+ from the multiple-peck (high-effort) trials and the S+ from the one-peck (low-effort) trials, and likewise between the two respective S− stimuli. Using a slightly different procedure that permitted assessment of the relative aversiveness of low versus high effort, Experiment 6 again revealed a pattern of indifference despite showing that pigeons took considerably longer to begin pecking on high- than on low-effort trials. Our findings call into question the reliability of the original findings and the sufficiency of the hypothesized within-trial contrast mechanism to produce them.